Cobertura da vegetação ripária e macrófitas aquáticas nos subsistemas da planície de inundação do alto rio Paraná : a disponibilidade influi na assimilação por Prochilodus lineatus (Characiformes: Prochilodontidae)? - Sarragiotto, Mariana Cristina (2010)
The spatial variation in land cover (riparian vegetation and aquatic macrophytes) and the composition of δ13C of Prochilodus lineatus and its energy sources was investigated in subsystems Baia, Ivinheima and Paraná, in 2000, to assess whether the coverage area of vascular plants is proportional to the iliophagous assimilation. The transfer of carbon from these primary producers to P. lineatus was 76% in the the Paraná river floodplain, with spatial variation between the subsystems. Phytoplankton was the most assimilated energy source in Baia (46%) and Ivinheima (46%) subsystems and C4 macrophytes in Paraná subsystem (34%). The vegetation cover was higher in Ivinheima (52%) subsystem and lowest in Baia (13.7%). The coverage of vascular plants had no corresponding relationship with assimilation and the capture of P. lineatus. The preferential assimilation of phytoplankton occurred in the subsystems of smaller and larger vegetation area and the fish capture demonstrated little variation between them. These results show the selectivity on phytoplankton assimilation by P. lineatus and suggest the dependence of the abundance of the fish by the producer´s. The mechanisms that regulate the selective assimilation of phytoplankton by this specie are not clear yet and should be investigated for inclusion in the strategies of management, conservation and fisheries production of P. lineatus, a species of great ecological and commercial importance. Natural and anthropogenic changes are intense in the study area, with effects on the availability of carbon sources of the species and monitor their assimilation of energy must be frequent.